2019
DOI: 10.1038/s41598-019-46797-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse tail lymphedema model for observing lymphatic pump failure during lymphedema development

Abstract: It has been suggested that many forms of secondary lymphedema in humans are driven by a progressive loss of lymphatic pump function after an initial risk-inducing event. However, the link between pump failure and disease progression has remained elusive due to experimental challenges in the clinical setting and a lack of adequate animal models. Using a novel surgical model of lymphatic injury, we track the adaptation and functional decline of the lymphatic network in response to surgery. This model mimics the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…Interestingly these differences were most pronounced in cell populations known to be highly migratory, including monocytes and macrophages. Previous studies in our lab have shown that contractile function in the intact lymphatic vessel in this model decreases significantly by the 2W timepoint [ 19 ]. The loss of preferential proliferation and migration in the intact vessel dLN may be due to loss of function in the intact vessel [ 19 ].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly these differences were most pronounced in cell populations known to be highly migratory, including monocytes and macrophages. Previous studies in our lab have shown that contractile function in the intact lymphatic vessel in this model decreases significantly by the 2W timepoint [ 19 ]. The loss of preferential proliferation and migration in the intact vessel dLN may be due to loss of function in the intact vessel [ 19 ].…”
Section: Resultsmentioning
confidence: 86%
“…To study how various immune cell populations in dLNs change during lymphedema progression, we used a single vessel ligation lymphedema mouse tail model developed by our group [ 19 ]. This model leaves one collecting vessel trunk intact, allowing for drainage from the site of injury to the LN downstream of the functioning vessel, referred to as the intact vessel dLN, while the LN downstream of the ligated vessel, referred to as the injured vessel dLN, experiences inhibited lymph inflow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multichromatic NIR imaging was carried out using a customized NIR setup 17,24 . Briefly, the system consists of a cooled EMCCD camera (Evolve eXcelon, Photometrics) attached to a stereomicroscope with adjustable zoom (MVX10, Olympus), a shutter-controlled xenon arc light source (Lambda LS, Sutter Instrument Company), and a manual filter wheel equipped with standard Cy5.5 and ICG-B filter cubes (Chroma Technology).…”
Section: Nir Imaging Setupmentioning
confidence: 99%
“…Near-infrared imaging of indocyanine green (ICG) is a standard procedure in the clinical assessment of the lymphatic system [26][27][28][29]. ICG based NIR imaging has been used both to evaluate lymphatic function in animal models and NIR functional imaging [20,[29][30][31], nevertheless, it has not been used as a standardized tool for pre-and intraoperative lymphangiographic navigation to guide a precise lymphatic injury for in-vivo studies.…”
Section: Introductionmentioning
confidence: 99%